Modern journalism in the digital ecosystem: theoretical approaches of foreign media researchers - Hradziushka, Aleksandr A. (Journal of the Belarusian State University. Journalism, 2022)
The main theoretical aspects of the transformation of journalism in the digital space are systematised. The evolution of scientific ideas about the essence of the term «digital journalism» and their reflection in the foreign theory of journalism are considered. The key concepts of studying journalism in the digital ecosystem are identified. The transformation of views on the problem under study is considered. The dynamics of theoretical thought is characterised. The periodisation of journalism researches in the digital space is proposed. Institutional changes in journalism in the context of the global transformation of the media industry are revealed. The thesis that technological changes lead to digital modification of the media ecosystem is substantiated.